Contribution of Oral Hygiene and Cosmetics on Contamination of Gluten-free Diet: Do Celiac Customers Need to Worry About?. Issue 1 (January 2019) - Verma, Anil K.; Lionetti, Elena; Gatti, Simona; Franceschini, Elisa; Catassi, Giulia Naspi; Catassi, Carlo
ABSTRACT: Objectives: The only available treatment for celiac disease (CD) is the gluten-free diet. It is unclear whether the presence of gluten in oral hygiene products and cosmetics that are applied on the mouth is a reason of concern for CD patients. The aim of this study was to test the level of gluten contamination in oral hygiene and cosmetic products available in the Italian market. Methods: A total of 66 products (toothpastes = 37; dental tablets = 2; mouthwashes = 5; lip-balms = 10; lipsticks = 12) labelled gluten-free or with unknown gluten content were randomly collected from different supermarkets and pharmacies. The gluten quantification was determined by the R5 ELISA method approved by EU regulations. Results: Out of 66 oral hygiene and cosmetics, 62 products (94%) were found to be gluten-free (gluten level <20 ppm), while 4 (6%) (toothpastes = 3; lipsticks = 1) showed a gluten level >20 ppm (toothpastes: 20.7, 31.4, and 35 ppm; lipstick: 27.4 ppm). None of the selected products had ingredient derived from wheat, barley, or rye. Conclusions: Gluten contamination is currently not an issue in a wide array of cosmetic and oral hygiene products that are commonly in the market. Abstract : Supplemental Digital Content is available in the text